Mapping QTL controlling soybean seed sucrose and oligosaccharides in a single family of soybean nested association mapping (SoyNAM) population. (21st December 2020) - Salari, Mohammad Wali; Ongom, Patrick Obia; Thapa, Rima; Nguyen, Henry T.; Vuong, Tri D.; Rainey, Katy Martin
Abstract: The meal value of Soybean for monogastric animals is determined partly by sucrose, raffinose and stachyose. Of these, sucrose is desirable, while raffinose and stachyose are indigestible, causing flatulence and abdominal discomfort. The objective of this study was to identify quantitative trait loci (QTL) controlling seed sucrose, raffinose, and stachyose in a set of 140 SoyNAM (Nested Association Mapping) recombinant inbred lines (RILs), developed from the cross between lines IA3023 and LD02‐4485. A total of 3, 038 SNP markers from the Illumina SoyNAM BeadChip SNP were used to map the QTLs for sucrose and the RFOs, raffinose, and stachyose. Significant genotypic differences ( p  < .001) among RILs were observed for sucrose, raffinose and stachyose contents across years. A 3038 Illumina SoyNAM BeadChip SNPs identified three QTLs for sucrose, one on chromosome 1, explaining 10% variance and two on chromosome 3 each explaining 22%. Raffinose QTL was detected on chromosome 6, explaining 6% variance. The mapped QTLs were novel and spanned regions harbouring candidate genes with roles in plant growth including seed development.